Effects of cigarette smoke on the aggravation of ovalbumin-induced asthma and the expressions of TRPA1 and tight junctions in mice. (July 2021) - Sun, Yu-bo; Liu, Mo; Fan, Xin-sheng; Zhou, Li-ping; Li, Meng-wen; Hu, Fang-yuan; Yue, Qin-fei; Zhang, Yi-ming
Highlights: CS aggravated airway inflammation and injury induced by OVA. CS aggravated the destruction of TJs protein in lung tissues of OVA-induced asthmatic mice. The increasing expression of TRPA1 caused by OVA+CS was related to the destruction of TJs and airway injury. Abstract: The occurrence of asthma is closely related to environmental factors such as cigarette smoke (CS), one of the common risk factors. Environmental stimuli have the potential to activate transient receptor potential ankyrin 1 (TRPA1) and cause or aggravate asthma. The destruction of tight junctions (TJs) between airway epithelial cells by environmental stimuli in asthma has been researched. It is worth exploring whether CS can injury TJs and aggravate asthma by activating TRPA1. The objective of this study was to investigate the aggravation of CS on ovalbumin (OVA)-induced asthma related phenotypes and TJs expression in mice, and to explore the relationship between TRPA1 and the expression of TJs protein. Female wild type (WT) C57BL/6 mice, induced by OVA, CS and OVA plus CS (OVA + CS) respectively, were used to establish a 42-day asthma model, and mice with TRPA1 knockout (TRPA1 −/− ) were treated in the same way. This study detected the number of inflammatory cells in peripheral blood and bronchoalveolar lavage fluid (BALF), the levels of IL-4, IL-5, IL-13 in BALF, enhanced pause (Penh) of lung function, pathological changes and the gene and protein expressions of TRPA1 and TJs (including ZO-1, Occludin and Claudin-2) in lung tissues. Compared with normal saline (NS) group, WT mice in the OVA group and OVA + CS group were significantly higher in asthma related phenotypes. The WT-OVA + CS group also showed higher Penh value, levels of IL-5 and IL-13 in BALF and lung tissue injury scores when compared with the WT-OVA group and WT-CS group. However, WT-OVA + CS group mice had significantly larger number of neutrophils in BALF than the WT-OVA group, and had larger number of eosinophils in peripheral blood and higher levels of IL-4 in BALF than the WT-CS group. Meanwhile, compared with the WT-NS group, the expressions of TRPA1 and Claudin-2 in lung tissues increased in other three groups while their expressions of ZO-1 and Occludin decreased, among which, the WT-OVA + CS group showed more remarkable changes. Compared with the WT-OVA + CS group, mice in the TRPA1 −/− -OVA + CS showed a significant decrease in the number of inflammatory cells, levels of IL-4, IL-5 and IL-13 in BALF, Penh value and lung tissue injury score, and a downregulation of Claudin-2 expression while an upregulation of ZO-1 and Occludin expressions. In addition, the airway inflammation and injury, and the expressions of ZO-1, Occluding and Claudin-2 expressions were found with no statistic differences between TRPA1 −/− -OVA group and TRPA1 −/− -OVA + CS group. These results suggest that CS has aggravated the airway inflammation, pathological damage and destruction of TJs in airway epithelium of OVA-induced asthmatic mice, the processes of which are related to the increase of TRPA1 expression.